Enamel Surface Remineralization Effect by Fluorinated Graphite and Bioactive Glass-Containing Orthodontic Bonding Resin - Hyung-Jin Nam (Materials, 2019)
All orthodontic appliances are potentially cariogenic. The plaque around the orthodontic appliance can make demineralization on tooth surface causing white spot lesion (WSL). The most effective method to prevent WSL is Fluoride appliance and gargling, but this requires patient cooperation, which consumes additional treatment time and cost. As suggested in this study, biomaterials like bioactive glass and fluorinated graphite (FGt) having antibacterial and anti-demineralization ability effective and easy to use in the clinic. To clinically use orthodontic bonding resins containing Graphite Fluoride BAG (FGtBAG), its properties, biological stability, antimicrobial activity, and remineralization effect must be verified. BAG was mixed with 2.5% FGt containing 51 to 61% fluorine. This mixture was mixed with the CharmFill Flow (CF) in the ratios of 1, 3, and 5 wt%. Microhardness and shear bond strength tests were performed to evaluate its mechanical properties. MTT (3-(4, 5-dimethyl thiazol-2-yl)-2, 5-diphenyl tetra) assay was performed for evaluating its safety. Streptococcus mutans, which is major cariogen by producing lactic acid, was evaluated for antibacterial ability of reducing WSL. In addition, x-ray images were obtained by CBCT (Cone beam computed tomography) after a pH cycle. The remineralization effect was verified in vivo and by Image J. FGtBAG did not differ significantly from CF in mechanical tests. The MTT assay found no significant differences between the groups. The antibacterial activity of FGtBAG at 24 h and 48 h was significantly higher than that of CF. The fluoride release rate tended to increase with the FGtBAG content. The pH cycle results showed that FGtBAG had higher concentration-dependent remineralization effect than CF. The results of this study suggests that orthodontic resins containing FGtBAG can prevent WSL owing to their antibacterial activity and remineralization effect.